The constitutional state - Barber, N. W. (Nicholas William) (Oxford : Oxford University Press, 2010)
'The Constitutional State' provides an account of the nature of the state & its constitution. This account casts light on some of the central puzzles faced by writers on constitutions - such as the possibility of states to undertake actions & form intentions, & the moral significance of these action for the state's citizens.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constitutional law; State, The